MEMBANGUN KARAKTER MAHASISWA PGSD: MENYONGSONG PERWUJUDAN SUMBER DAYA MANUSIA BERBASIS MASYARAKAT EKONOMI ASEAN - Ana Fitrotun Nisa (Universitas Sarjanawiyata Tamansiswa, 2015)
Â Abstract:Indonesiais a countryin Southeast Asiaand a member of ASEAN. As a manifestationofeconomic integration ofcountriesin theASEAN, Indonesia is included in ASEANEconomic Community(AEC). With AEC, it is not only in trade of goods sector which need to adjust, but also in services sector. Public may work freely in other countries in accordance with their abilities or skills and requirements required in the country. In facing AEC manifestation, education must also be responsive in preparing educators who have a human resources-based AEC. Teacher is a figure who is always been being a role model by students wherever he/she is. Teachers also enormously contribute in succeeding national education goals. Since position of teachers are significant in realizing education, then character of teachers needs to be considered in order to be a figure corresponding to the requirements. In realizing it, a teacher should: (1) Have a creative thought and has new innovations appropriate with his/her characteristic; (2) Be able to establish a network with the various parties; (3) Have language skills and mastering culture in accordance with